Towards responsible geographies of memory: complexities of place and the ethics of remembering - Till, Karen E.; Kuusisto-Arponen, Anna-Kaisa (ERDKUNDE, 2015)
Debates about the meanings of place often emerge when unsettled pasts resurface unexpectedly in ways that dislocate present-day land-uses. Such was the case for the IGU 2011 Regional Meeting in Chile, which was held in Santiago's Military Academy. When considering the geographical scholarship about place and memory, the debates resulting from the conference should not be surprising. Geographers have long examined the controversial processes of social memory and forgetting at places marked by state-perpetrated violence and have noted the unpredictability of group memory due to the translocal nature of how places are connected to peoples and pasts through socio-political networks, cultural and economic connections, and personal and shared emotional geographies. To understand the complexities of ethical relationships we have with places marked by violence, we look to another example, the Memorial and Museum Camp Westerbork in the Netherlands. The past is never ‘set in stone’ or stable in present-day landscapes. Just as the narratives associated with remembering and forgetting the past may change through time, so too do the spatial contexts of memory. When space-times shift unexpectedly, new social discussions about the significance of the past in the present may emerge. With both examples in mind, we conclude by making a case for the creation of “responsible geographies of memory”. We argue that it is our professional responsibility as geographers and our obligation as global citizens to: 1) acknowledge that landscapes often function as places of critical testimony for survivors; 2) problematize singular claims to the authenticity of place made through universal narratives and seemingly stable material landscapes; 3) create safe spaces of listening, wherein stories about place can be articulated and acknowledged by various stakeholders, while recognizing the moral complexities in representing violence through textual, visual and embodied means; and 4) recognize the progressive potential of places as cosmopolitan spaces of encounter and learning. By treating places marked by difficult pasts as cosmopolitan, hosts and visitors are invited to engage critically with the unfolding processes of memory politics, and adopt respectful approaches toward justice that includes caring for places and peoples in the past and present.